Neon soft x-ray yield optimization from PF-SY1 plasma focus device - Akel, M.; Al Hawat, Sh.; Lee, S. (Springer US, 2011)
Based on the consideration of that for operation of the plasma focus in neon, a focus pinch compression temperature of 200–500 eV (2.3 × 106–5 × 106 K) is suitable for good yield of neon soft X-rays (SXR), numerical experiments have been investigated on the plasma focus device PF-SY1 using the latest version Lee model code. The Lee model code is firstly applied to characterize the PF-SY1 Plasma Focus. Keeping the bank parameters and operational voltage unchanged but systematically changing other parameters, numerical experiments were performed finding the optimum Y sxr was 0.026 J. Thus we expect to increase the neon Y sxr of PF-SY1 from its present typical operation; without changing the capacitor bank and the electrode configuration merely by changing the operating pressure. The Lee model code was also used to run numerical experiments on PF-SY1 with neon gas for optimizing soft X-ray yield with reducing L 0, varying z 0 and ‘a’. From these numerical experiments we expect to increase the neon Y sxr of PF-SY1 with reducing L 0, from the present 0.026 J at L 0 = 1600 nH to maximum value of near 26 J at an achievable L 0 = 10 nH.